Prisoners' Perceptions About Postrelease Employment in Romania: Studying the Role of Human Capital and Labelling Factors in Explaining Optimism and Pessimism - Dâmboeanu, Cristina (International journal of offender therapy and comparative criminology, 2019)
Prior evidence shows that prisoners' beliefs and perceptions have profound implications for their postprison success. This study shows which prisoners are more or less optimistic about their postrelease employment prospects and for what reason. Specifically, this study examines how pessimistic prisoners are about finding a job, finding an unskilled job, and finding a minimum-wage job. It also reveals whether variables drawn from labelling and human capital theories can explain between-individual differences in these perceptions. Using survey data on 154 Romanian prisoners, we find substantial differences in optimism. These differences are partly explained by prisoners' criminal history and human capital, but more so by prisoners' expectations about the importance of these characteristics in the hiring process. Policy implications are discussed.